Solution of Fractional Inventory Model with Price Dependent Demandusing Homotopy Perturbation Method - M.V. Jeyanthi, P.S. Sheik Uduman, Dowlath Fathima (International Journal of Advanced Science and Technology, 2020)
In this paper, an inventory model is developed with price dependent demand and exponential deterioration rate. The model is enhanced to fractional derivative using Caputo Derivative method and solved by using Homotopy Perturbation Method (HPM). The optimum solution is determined with the help of numerical example and sensitivity analysis. Keywords–Exponential Deterioration Rate, Price Dependent Demand, Homotopy Perturbation Method